Pengaruh Ekstraksi Daun Jati Muda Dengan Variasi Jenis Pelarut Dan Lama Penyimpanan Terhadap Stabilitas Kertas Indikator Asam Basa Alternatif - Wibowo, Vina Noviasanti Putri, Triastuti , S.Si, M.Si (2017)
Acid-base indicator is a substance that can indicate the nature of the acid, alkaline and neutral solution. Teak leaf especially the young ones have a red pigment derived from anthocyanins and thus potentially as an alternative to acid-base indicator. This study aimed to determine the effect of solvent type on the color change ph indicator paper and paper storage time influence the color stability of the resulting paper ph indicator of young teak leaf extract after being tested. This study used an experimental method with a completely randomized design (CRD) using two factors, namely the type of solvent treatment and storage of paper. The type of solvent used is Ethanol 96% and Ethanol 96% + HCl 1% with a variation of the paper storage time of 0, 5, 10 and 15 days. The parameters in this study is the change in color of paper ph indicator of young teak leaf extract after dipped in a solution of acid-base indicator paper and color stability against storage time is different. The results showed that the variation of solvent type affect the color change of the indicator paper, ethanol 96% + HCl 1% produce more contrast colors distinguish the acidic or alkaline solution that is red in acidic solution and army-green moss green in alkaline solution. Old paper storage to give effect to the color stability after being tested. The color change is more stable in 96% ethanol + HCl 1%, after storage for up to 15 days of color fading, but still be able to distinguish between the nature of the acid with a base. Keywords: Anthocyanins, young teakleaves, acid-base indicators, solvent type, duration of paper storage